Hubungan Karakteristik Kontak Erat dengan Pengetahuan, Sikap, dan Perilaku Pencegahan Tuberkulosis: Studi Potong Lintang di Puskesmas Kenarilang, Alor, Nusa Tenggara Timur - Abadi, Hanif; Lily, Ezra Maraben (UI Scholars Hub, 2025)
Indonesia ranks second globally in the number of tuberculosis (TB) cases, accounting for 10% of all global cases. In the working area of Kenarilang Public Health Center, 951 confirmed TB cases were recorded as of October 2024. Close contacts of TB patients are at high risk of infection and may become new sources of transmission if not properly managed. Knowledge, attitudes, and practices (KAP) among close contacts play a crucial role in TB prevention, aligning with the target of TB elimination by 2030. This study aims to determine the relationship between the characteristics of close contacts and their KAP levels in TB prevention. This quantitative study used a cross-sectional design involving 26 respondents in the working area of Kenarilang Public Health Center in November 2024. Data were collected using a structured KAP questionnaire and analyzed descriptively and bivariately. Chi-square test, Fisher’s exact test, and logistic regression test were used according to data type and distribution. A total of 65.38% of respondents demonstrated good knowledge. Attitudes were evenly split between positive and negative (50%), with the highest agreement on the importance of preventive therapy (89.74%). Meanwhile, 57.69% showed good preventive practices. Bivariate analysis revealed significant associations between age and practices (OR=1,244; p=0,017), income and attitude (p=0.048), residence and practices (p=0.014), and marital status and practices (p=0.020). Demographic factors play a role in shaping responses to KAP aspects of TB prevention, although several gaps remain. Data-driven interventions targeting specific demographic groups may be effective strategies for TB control. Keywords : Knowledge, Attitude, Practice, Close Contact, Tuberculosis Prevention